The Influence of Democratic Leadership Style, Work Discipline, and Work Motivation on Employee Performance at PT. Sinotrans - Sinta Sundari Heriyanti; Erlin Apriyani (Journal of Research in Business, Economics, and Education, 2021)
This study aims to determine the effect of democratic leadership style on employee performance, work discipline on employee performance and work motivation on employee performance. This study uses a quantitative approach, the number of samples taken is 50 people consisting of all employees of PT. Sinotrans. Data was collected by distributing questionnaires to respondents via google form. The data test in this study used validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, coefficient of determination analysis and multiple linear regression with the help of SPSS program. The results of this study indicate that democratic leadership style has a positive and significant effect on employee performance, work discipline has a positive and significant effect on employee performance and work motivation has a positive and significant effect on performance.